RELATHIONSIP BETWEEN MONEY VELOCITY AND INFLATION TO INCREASING STOCK INVESTMENT RETURN: EFFECTIVE STRATEGIC BY JAKARTA AUTOMATED TRADING SYSTEM NEXT GENERATION (JATS-NG) PLATFORM - Nur Ilham, Rico; Arliansyah, Arliansyah; Juanda, Reza; Multazam, Muhammad; Saifanur, Andri (CV. Radja Publika, 2021)
This study aims to formulate strategies to avoid macroeconomic risks in investing in the Indonesian capital market so that more people will be able to trade in financial instruments traded in the Indonesian capital market using an integrated online transaction system. This type of research is quantitative descriptive with the research population of 20 State-Owned Enterprises (BUMN) listed on the Indonesia Stock Exchange. The type of data in this study is time series data taken from 2016 to 2020 by conducting a documentation study conducted on the publication of annual financial statements (Financial Statements), so that the target population is 40 (8 Companies x 5 Years) annual financial report data for the research sample. The data analysis method in this study uses Moderate Regression Analysis (MRA) and data analysis uses the Smart PLS statistical software. The outputs of this research are publications of reputable international journals, international proceedings and reference books for ISBN certified research results with TKT level 3.